The great recession, youth unemployment and inequalities in psychological health complaints in adolescents: a multilevel study in 31 countries - Rathmann, Katharina; Pförtner, Timo-Kolja; Hurrelmann, Klaus; Osorio, Ana M; Bosakova, Lucia; Elgar, Frank J; Richter, Matthias (International journal of public health, 2016)
OBJECTIVES: Little is known about the impact of recessions on young people's socioeconomic inequalities in health. This study investigates the impact of the economic recession in terms of youth unemployment on socioeconomic inequalities in psychological health complaints among adolescents across Europe and North America. METHODS: Data from the WHO collaborative 'Health Behaviour in School-aged Children' (HBSC) study were collected in 2005/06 (N = 160,830) and 2009/10 (N = 166,590) in 31 European and North American countries. Logistic multilevel models were used to assess the contribution of youth unemployment in 2009/10 (enduring recession) and the change in youth unemployment (2005-2010) to adolescent psychological health complaints and socioeconomic inequalities in complaints in 2009/10. RESULTS: Youth unemployment during the recession is positively related to psychological health complaints, but not to inequalities in complaints. Changes in youth unemployment (2005-2010) were not associated with adolescents' psychological health complaints, whereas greater inequalities in complaints were found in countries with greater increases in youth unemployment. CONCLUSIONS: This study highlights the need to tackle the impact of increasing unemployment on adolescent health and health inequalities during economic recessions.
Keywords: Mental Health; North America; Humans; Unemployment; guanosindifosfát; Health inequalities; Severní Amerika; dítě; socioekonomické faktory; rozložení podle pohlaví; Child; duševní zdraví; Female; nezaměstnanost; Subjective health; lidé; Europe; ekonomická recese; Health Status Disparities; Socioeconomic Factors; Economic Recession; věkové rozložení; víceúrovňová analýza; Guanosine Diphosphate; ženské pohlaví; Youth unemployment; Male; Recession; Adolescent; Adolescence; Age Distribution; Multilevel Analysis; Sex Distribution; disparity zdravotního stavu; mužské pohlaví; Evropa; Multilevel analysis; mladiství